Ensaio Clínico Randomizado para avaliar o impacto da adição de quimioterapia metronômica na sobrevida livre de eventos de pacientes recém-diagnosticados com osteossarcoma de alto grau, ressecável, de extremidade, não metastático: Uma colaboração do Grupo Latino Americano para Tratamento de Osteossarcoma - Senerchia, Andreza Almeida [UNIFESP] (2021)
The aim of this study was, therefore, to analyze whether the addition of cyclophosphamide and methotrexate to a metronomic chemotherapy regimen as maintenance therapy after postoperative methotrexate, adriamycin and cisplatin would improve event-free survival in patients with non-invasive osteosarcoma. metastatic of the extremities. Cyclophosphamide and methotrexate were selected as metronomic agents because of their availability, presumably low toxicity, low cost, and preliminary data suggesting multisegment therapeutic effects.